2015
DOI: 10.1016/j.eurpsy.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

On the correlation between perceptual inundation caused by realistic immersive environmental auditory scenes and the sensory gating inventory in schizophrenia

Abstract: An evaluation of the external validity of the SGI was obtained through listening tests. The ability to control acoustic parameters of each of the realistic immersive environmental auditory scenes might in future research make it possible to identify acoustic triggers related to perceptual inundation in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It objectifies the perceptual abnormalities and functional and psychosocial consequences of sensory gating. SGI could confirm anomalies of sensory gating and perceptual inundation in schizophrenia (Micoulaud-Franchi and Vion-Dury, 2013;Micoulaud-Franchi et al, 2014;El-Kaim et al, 2015), attention-deficit hyperactivity disorder (ADHD) (Sable et al, 2012;Micoulaud-Franchi et al, 2014; and Tourette syndrome (Sutherland Owens et al, 2011).…”
mentioning
confidence: 99%
“…It objectifies the perceptual abnormalities and functional and psychosocial consequences of sensory gating. SGI could confirm anomalies of sensory gating and perceptual inundation in schizophrenia (Micoulaud-Franchi and Vion-Dury, 2013;Micoulaud-Franchi et al, 2014;El-Kaim et al, 2015), attention-deficit hyperactivity disorder (ADHD) (Sable et al, 2012;Micoulaud-Franchi et al, 2014; and Tourette syndrome (Sutherland Owens et al, 2011).…”
mentioning
confidence: 99%
“…This could be exacerbated by the high variety and intensity of auditory stimuli present in urban environments ( Gottschalk, 1972 , Landon et al, 2016 , Wright et al, 2014 ). Patients with schizophrenia appear to have increased responses to noises from urban environments compared to healthy controls ( Tregellas et al, 2009 , Tregellas et al, 2007 ) and have more difficulty integrating auditory stimuli into a single coherent understanding, particularly when stimuli include negative or frightening emotional valence ( El-Kaim et al, 2015 ). These stimuli in urban environments are less predictable and more intense than in rural environments and, over time, the cumulative impact of these stimuli appear to increase risk, potentially due to compensatory neural alterations ( Light and Braff, 2003 , McGhie and Chapman, 1961 , Nelson et al, 2014 , Postmes et al, 2014 ).…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%
“…Some authors have reported higher sensibility to urban noise among patients suffering from schizophrenia (Tregellas et al, 2007;Tregellas, Ellis, Shatti, Du, & Rojas, 2009). Furthermore, a recent study (El-Kaim et al, 2015) using realistic immersive environmental auditory scenes, established that schizophrenia patients, shown to have a higher sensitivity to nonstationary sounds (i.e with high rate of impacted acoustic features), had greater difficulties in combining stimuli into coherent representation than subjects from a control group, especially when it comes to negative or frightening emotional valence of the stimulus. These elements suggest a possible role for acoustic stimulations in the emergence or the persistence of psychotic symptoms.…”
Section: The Concept Of "Urban Stress"mentioning
confidence: 99%